2019
DOI: 10.7575/aiac.alls.v.10n.4p.153
|View full text |Cite
|
Sign up to set email alerts
|

CLIL and Productive Vocabulary Acquisition in the Czech Context

Abstract: This paper sheds light on productive vocabulary development in classes of CLIL (content and language integrated learning). Participants in the study were pupils of lower-secondary school (aged 11-15) in the Czech Republic having experienced CLIL instruction in History or Civics. The investigation was aimed at measuring vocabulary acquisition gained during a year of CLIL. Half of the pupils in the experimental group already had one year of CLIL experience prior to the experiment; the second half of the pupils s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…This statement was the most preferred, indicating that all students agreed that critical reading material could stimulate the learning to be more extensive and have a varied vocabulary. Gierlinger and Wagner (2016) and Reynaert (2019) found that CLIL classrooms could benefit learners in their acquisition of vocabulary in the target language. Implicitly, the highest need for integrating the CLIL principle into critical reading material can be seen in the visible growth in receptive and productive vocabulary (Karabassova, 2018).…”
Section: Student Perceptions Of Clil-based Critical Readingmentioning
confidence: 99%
“…This statement was the most preferred, indicating that all students agreed that critical reading material could stimulate the learning to be more extensive and have a varied vocabulary. Gierlinger and Wagner (2016) and Reynaert (2019) found that CLIL classrooms could benefit learners in their acquisition of vocabulary in the target language. Implicitly, the highest need for integrating the CLIL principle into critical reading material can be seen in the visible growth in receptive and productive vocabulary (Karabassova, 2018).…”
Section: Student Perceptions Of Clil-based Critical Readingmentioning
confidence: 99%